Stock Liquidity Effect on Mergers & Acquisitions Returns Performance - , Wisnu Aji Wicaksono; , Dr. Ben Tims ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research analyzes the effect of acquirer and target firmsâ stocks liquidity to acquirersâ returns performance. Amihud illiquidity is used as a stock liquidity proxy, while cumulative abnormal returns (CARs) and buy- hold abnormal returns (BHAR) are used as returns performance proxy. Results show that acquirerâs stock liquidity has strong and significant negative effect in surrounding announcement date, in one-month, two-years, and three-years post-announcement date. In other hand, targetâs stock liquidity has positive effect in surrounding announcement date and one- month post-announcement date. In a multiple regression analysis, acquirerâs stock liquidity effects which are controlled by firm size and firm leverage have prediction values between 15.7% and 24.3% in short-term returns performance and around 7% in two-years and three-years post- announcement returns performance.